Unexplored agronomic, socioeconomic and policy domains for sustainable cotton production on small landholdings: a systematic review - Tlatlaa, Jacob Shauri; Tryphone, George Muhamba; Nassary, Eliakira Kisetu (Frontiers in Agronomy, 2023)
Cotton productivity continues to be disputed, despite rapid advancements and widespread technologies. These uncertainties remain to be critically addressed in a broad spectrum focusing on domains at the global level. Therefore, this systematic review provides an overview of the existing advancements in knowledge, skills, and technologies for sustainable cotton production on small landholdings. Specifically, the areas of the cotton chain examined are threefold: -(1) Explore disguised agronomic practices to be endowed for sustainable cotton production on small landholdings; (2) Explore socioeconomic settings based on their disparities in contributing to sustainable cotton production on small landholdings; and (3) Explore existing and feasible institutional policies to be enforced for sustainable cotton production on small landholdings. This review shows that worldwide cotton production involves conventional and organic systems, at the expense of the traditional system. Heavy uses of nitrogenous fertilizers and pesticides are the common practices in conventional systems, with some adoptions of precision agriculture practices, and genetically modified varieties. Rotation and intercropping with early-maturing food crops are also identified viable options to improve farmers' attitudes toward adopting cotton-producing technologies. In socioeconomics, farmers' livelihoods are improved by income generation from sales of cotton and labour in the cotton industry. Gender equity in the cotton industry prioritizes females over males, as females display a group with a higher level of technology adoption. Generally, clear institutional policies governing the cotton industry are globally paucity. Furthermore, efforts to sensitize sustainable cotton production are still highly questionable and challenged by the superseding climate changes.